A cultura do roteiro no cinema brasileiro dos anos 1950 : uma introdução = The culture of the screenplay in Brazilian cinema in the 1950s: an introduction - Romanzoti, Natasha, 1989- (2018)
Orientador: Alfredo Luiz Paes de Oliveira Suppia